Investigating blend morphology of P3HT:PCBM bulk heterojunction solar cells by classical atomistic simulations – Progress and prospects. Issue 2 (2nd July 2020) - Munshi, Joydeep; Balasubramanian, Ganesh
ABSTRACT: This report presents recent progress in computational modeling efforts on blend morphology of P3HT:PCBM-based bulk heterojunction (BHJ) thin-film organic solar cells (OSCs). Improving power conversion efficiency (PCE), developing cost-effective fabrication methods and designing suitable electron donor and acceptor materials have been the most critical issues related to organic solar cell research in the past decade. Mixtures of poly-(3-hexyl-thiophene) (P3HT) and phenyl-C61 -butyric acid methyl ester (PCBM) as electron-donor and electron-acceptor materials, respectively, have been widely investigated over the past decade. Despite the advances in experimental techniques, like atomic force microscopy (AFM), transmission (TEM) and scanning (SEM) electron microscopy and electron tomography, acquiring three-dimensional (3D) nanoscale morphological information from BHJ devices is challenging due to poor contrast in electron microscopy techniques of organic materials. Atomistic simulations are able to provide insights into the dynamics of blend morphology of OSCs and overcome the experimental challenges. In addition, coarse-grained molecular dynamics (CGMD) simulation is able to simulate structures approaching experimental length scales and processing conditions. Here we discuss about the insights that have been gained from classical atomistic simulations with an emphasis on CGMD modeling techniques developed in recent years. Effect of solution processing conditions and thermal annealing process on the morphology and dynamics of BHJ devices are reviewed as well. Finally, the future scope of molecular modeling efforts to tackle current and anticipated challenges in organic photovoltaic technologies are suggested, with a goal to identify the opportunities that remain open to be addressed by atomistic computations of OSCs.